Farmer’s Motivational Factor on Farmers Managed-Extension Activities (FMA)’S Adoption in Temanggung Regency - Ihsaniyati, Hanifah; Setyowati, Nuning; Sutarto, Sutarto; Lestari, Eny (Journal of Rural Indonesia [JORI], 2015)
Farmers Managed-Extension Activities (FMA) provides substantial benefits to the farming community empowerment, especially for the improvement of information services for farmers. Consider the benefits and objectives are achieved , then this great program requires rigorous evaluation and mentoring to monitor progress . Previous survey showed no understanding of the diversity of farmers’ level , the percentage decrease in the number of farmers who apply from 2010 (64.56 %) to the year 2011 (48.23 %), and parthnership between farmers and traders only 35.9 % (still small). On the other hand, there is saturation analysis tools in studies on adoption. Therefore, this study aimed to analyze the motivational factors of farmers against the FMA program. The method used in this research was models the Technology Acceptance Model using Structural Equation Models with analysis tools , namely PLS (Partial Least Square). The results showed (1) Perception of farmers to ease was not significantly related to the attitude of farmers towards FMA at a significance level of 0.43 (p value); (2) Perception of farmers on the benefits / uses significantly associated with attitudes of farmers towards FMA at the 0.01 level (p value), (3) ability to absorb farmers are not significantly related to the attitude of farmers towards FMA at a significance level of 0.48 (p value), (4) the diversity of the media associated significantly with the attitude of farmers towards FMA at the 0.01 signif- icance level (p value), (5) attitude significantly associated with implementing farmers ‘ intentions / FMA adoption at a significance level of 1.90539 E - 08 (p value), (6) intention farmers significantly associated with implementing farmers’ behavior/FMA adoption at a significance level of 3.14341 E - 08 (p value).Keywords : FMA, adoption, farmer,extension, empowerment